Manajemen Sumber Daya Energi Terbarukan : Optimalisasi PLTS-PLTB untuk Kelistrikan Berkelanjutan di Pulau Dudepo - Sudarmanto Hasan; Marini Susanti Hamidun; Dewi Wahyuni K. Baderan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Remote islands in Indonesia face significant challenges in achieving sustainable electricity supply. This study analyzes the technical and economic feasibility of implementing a hybrid Solar Power Plant (PLTS) and Wind Power Plant (PLTB) system on Dudepo Island, North Gorontalo Regency. With an average solar radiation of 5.2 kWh/m²/day and wind speed of 4.8 m/s, the hybrid system is designed to supply approximately 97% of local electricity demand with an efficiency of 85%. Simulations using HOMER Pro reveal an optimal configuration of 100 kW PLTS, 60 kW PLTB, and 300 kWh battery storage. Economic analysis indicates a Levelized Cost of Energy (LCOE) of IDR 1,450/kWh, more affordable than conventional diesel generators, with an eight-year payback period. The system’s implementation has enhanced community well-being by providing stable electricity access for education, healthcare, and economic activities. Moreover, it contributes to carbon emission reduction by up to 120 tons of CO₂ annually. Technical challenges and local human resource capacity necessitate sustainable management strategies, including technician training and IoT-based monitoring systems. This study offers recommendations for sustainable renewable energy development on remote islands as a model for environmentally friendly energy transitions.